The Role of Interpol in Addressing Transnational Cybercrime: A Review of Global Law Enforcement Collaboration in Southeast Asia - Kharisma, Dian; Swandiani, Ni Luh Putu Erika; Paliwang, Andi Nur Azizah Ardan (Perkara : Jurnal Ilmu Hukum dan Politik, 2025)
Transnational cybercrime is emerging today as a significant new worldwide menace, and in Southeast Asia, which is undergoing rapid digitalization but is marked by varying legal and technical capabilities. This paper, therefore, seeks to examine the role of Interpol in contributing strategically to strengthening law enforcement collaboration to combat cybercrime in Southeast Asia. The approach used in this study was descriptive qualitative, particularly case studies. It involved the collection of evidence from 30 official documents, Interpol reports, and scholarly literature dated from 2019 to 2024. The findings revealed that Interpol achieves this through intelligence exchange via the I-24/7 platform, technical training, and joint operations, such as Operation Haechi and Night Fury. Notwithstanding the auspicious connotation birthed by this collaboration, the variations in national capacities, dearth in digital infrastructure, as well as differences in legal frameworks, collectively form rather significant hurdles. Accordingly, this research provides a theoretical contribution towards enhancing understanding of the institutional role in regional cybersecurity and practical contributions in suggesting measures for optimizing cooperation in ASEAN. The interdisciplinary approach employed in this study is a significant innovation in bridging the gap in the literature on the role of international organizations in the fight against transnational cybercrime.